Why I Am an Accommodationist and Proud of It - Ruse, Michael (Zygon, 2015)
There is a strong need of a reasoned defense of what was known as the “independence” position of the science-religion relationship but that more recently has been denigrated as the “accommodationist” position, namely that while there are parts of religion—fundamentalist Christianity in particular—that clash with modern science, the essential parts of religion (Christianity) do not and could not clash with science. A case for this position is made on the grounds of the essentially metaphorical nature of science. Modern science functions because of its root metaphor of the machine: the world is seen in mechanical terms. As Thomas Kuhn insisted, metaphors function in part by ruling some questions outside their domain. In the case of modern science, four questions go unasked and hence unanswered: Why is there something rather than nothing? What is the foundation of morality? What is mind and its relationship to matter? What is the meaning of it all? You can remain a nonreligious skeptic on these questions, but it is open for the Christian to offer his or her answers, so long as they are not scientific answers. Here then is a way that science and religion can coexist.